Penerapan Problem Based Learning (PBL) untuk Meningkatkan Aktivitas dan Hasil Belajar IPA Siswa Kelas V SD Negeri 1 Sawah Lama Bandar Lampung TP 2019/2020 - Narni Kusmiyati (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2021)
The problem of this research is the low level of activity and learning outcomes in science for fifth grade elementary school students. The aim of the study was to improve science learning activities and outcomes through the use of Problem Based Learning (PBL) methods or problem-based learning for fifth grade elementary school students. The research method is Classroom Action Research (CAR). The research subjects are students of Class V Semester 1 of the 2019/2020 Academic Year. This research was conducted at SDN I Sawah Lama Bandar Lampung for fifth grade elementary school students. Research data obtained from observations of student learning activities and test results. The results showed an increase in student activity and learning outcomes from cycle to cycle, namely Cycle I learning activities on average Enough complete learning outcomes 62%, Cycle II learning activities on average Good learning outcomes completed 79%, Cycle III average learning activities Good learning outcomes complete 88%. Thus, the Problem Based Learning (PBL) method can improve students' activities and science learning outcomes.